RESERVOIR DISTRIBUTION AND SLOPE CHANNEL SYSTEM SEDIMENTATION MODEL ANALYSIS, A CASE STUDY OFFSHORE KUTAI BASIN, EAST KALIMANTAN - David Aruan, Johnny
Up to date the exploration and the exploitation in the deepwater area is considered as new matter, particularly in Indonesia. Only one deepwater basin of the some basins in Indonesia which has been proven to be able to produce hydrocarbon, namely offshore Kutai basin. Therefore the data and the study of the reservoir in the area need to be more explored in detail so therefore required more accurate and effective techniques. One of the techniques which used to help analyze and interpret the image of the geological subsurface condition is seismic amplitude attribute. Seismic signals which generally used to obtain reservoir information is amplitude. Interpretive approach to evaluate the reservoir from the attributes of the amplitude is using a simple assumption, namely bright spot on seismic data. This assumption based on the value of the amplitude, it will be higher when hydrocarbon saturation is high, gross thickness is becoming thicker (although with several complications with tuning effect). Extraction of seismic amplitude attributes RMS (Root Mean Square) is intended to see the extremely changes of the lithology, such as the existence of a reservoir layer. Seismic attributes extracted from 3D seismic data Pre-Stack Time Migration (PSTM) and three wells data (J-1, J-2 and J-3) for calibration this analysis. From the result of amplitude attributes RMS extraction is well detected by the amplitude on analysis window from 5 ms to up and 5 ms to down. The results of the analysis show the hydrocarbon potential in the slope channel system, at the Pliocene age, Kutai Basin, with the direction of deposition leads to the North West - South East (NW-SE), with a width ranging between 300 m - 1 km, 1–10 km long and a thickness ranging between 10-60 m. Using this methodology for modeling and reservoir distribution in the slope channel system can be used as an alternative interpretation of the reservoir in this area. The result of RMS amplitude extracted from the horizon which interpreted from the seismic data shows a fairly good correlation between amplitude and thickness of the reservoir and its validated with well data. The results of interpretation shows that currently the reservoir layer package it looks most likely is the result of the process of filling the valley (gully). The existence of layered reservoirs on the slope system is closely related to geomorphology and rise and fall of sea level.